Supporting the teachers’ communities with innovative initiations – The Future of Learning Concept - Farkas, Bertalan Péter; Györgyi-Ambró, Kristóf Áron (Tudásmenedzsment, 2022)
The concept of the Future of Learning Initiative (FLI) is about supporting everyday pedagogical practice with digital tools and collaborative learning for teachers. In this space, teachers collaborate with other teachers, learn from one another and reflect on their own practices together, and for this process, our organisation provides a thoroughly planned collaborative environment, methodology and know-how. We, at the Tempus Public Foundation (TPF) believe that pedagogy will become even more effective not by digital tools but by educators' thinking, the key to change is always the educators themselves and this is confirmed by all major international research as well as policy recommendations (EU, OECD, etc.). Approaching the FLI that has online services, we can say that the open online courses and online services have brought both the democratisation of adult education and the expansion of knowledge sharing opportunities. In addition to the many criticism of the open online content, it can certainly be said that online courses such as The Future of Learning MOOC have made a significant and remarkable contribution to the democratisation of adult education by sharing achievable learning outcomes with the wider public, with the key element of accessibility. With the Future of Learning Initiative, we have been able to raise knowledge management principles as well as practices that have been accumulated for more than a decade to a European level, and also set the goal of further internationalising the Future of Learning Initiative. In this summarising article we are going to introduce the FLI initiative and the FLI MOOC to the audience with details of the MOOC, the concept and methodology. The results of the different questionnaires, the theoretical background, and the measurements of the efficiency of the different tasks and assignments will be published in several different articles in the upcoming months and years.